Whose Responsibility Is It to Dismantle Medical Mistrust? Future Directions for Researchers and Health Care Providers. Issue 2 (3rd April 2019) - Jaiswal, Jessica
Abstract: Medical mistrust persists and appears to be growing. The public health literature on medical mistrust has largely focused on mistrust among Black and African American populations due to legacies of abuse and mistreatment, such as the infamous Tuskegee Syphilis Study. However, research is now emerging that explores mistrust among various populations and in varying contexts, and the literature now largely emphasizes the role of ongoing, present-day social and economic inequalities in shaping and sustaining mistrust, particularly among populations who experience staggering health disparities. This special issue showcased nine articles exploring medical mistrust among diverse populations, exploring a wide array of topics and spanning myriad methodologies. In addition to a rigorous systematic review of the literature, this issue covers several critical subareas of the health disparities literature, including preventative health screenings among Black men, discrimination and cultural factors among rural Latinx communities, health care satisfaction among Latina immigrant women, the complex relationship between HIV testing and "conspiracy beliefs" among Black populations, pre-exposure prophylaxis use among transgender women, the impacts of mass incarceration on HIV care, eHealth interventions to address chronic diseases among sexual minority men of color, and participatory research to engage underserved populations as co-researchers. The purpose of this article is to provide a brief summary of the nine manuscripts in this special issue and to outline some recommendations and future directions for research on medical mistrust.